Inductive Technologies of System-analytical Research as an Effective Tools in Complex Innovative Projects - Osypenko, V.V. (Індуктивне моделювання складних систем, 2012)
In this paper the some examples of the real system-analytic search direction projects of high complexity in different areas human activity are presented. The most problematic sides of modern technologies and their implementation have been formulated, in particular the high level of subjectivity in decisions making. Therefore, further improvement of the traditional information technologies and the development of new ones as well as the implementation of appropriate tools of such class of problems arise objectively as an acute problem of practice. Розглянуто приклади системно-аналітичних проектів інноваційного спрямування високого ступеня складності із різних сфер людської діяльності. Сформульовані проблемні сторони сучасних технологій виконання таких проектів і, насамперед, високий рівень суб’єктивності в процесах ухвалення рішень. Звідси, вдосконалення традиційних та розробка нових інформаційних технологій і витончених інструментів виконання такого класу завдань виникає об’єктивно, як гостра проблема практики. Рассмотрены примеры реальных системно-аналитических проектов инновационного направления высокой степени сложности из разных сфер человеческой деятельности. Сформулированы проблемные стороны современных технологий выполнения таких проектов и, в первую очередь, высокий уровень субъективности при принятии решений. Поэтому совершенствование традиционных и разработка новых информационных технологий и соответствующего инструментария